2006
DOI: 10.1002/job.350
|View full text |Cite
|
Sign up to set email alerts
|

Women, power, and sex composition in small groups: an evolutionary perspective

Abstract: SummaryDespite the massive influx of women into the workforce, women have made only minor gains into top management positions. Most explanations for this asymmetry have been based on sex differences in socialization and traits. We propose that an evolutionary psychological perspective offers an alternative explanation: sex differences in power are due to differences in the way men and women use influence behaviors in small groups, and these differences were sculpted, in part, by natural selection. This produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 84 publications
2
28
0
6
Order By: Relevance
“…The influence score for males was 2.76, while the influence score for females was 2.72, which presented no significant difference. This contradicts previous literature; 28,29 their findings indicate that males will exert more influence than females.…”
Section: Influencementioning
confidence: 59%
See 1 more Smart Citation
“…The influence score for males was 2.76, while the influence score for females was 2.72, which presented no significant difference. This contradicts previous literature; 28,29 their findings indicate that males will exert more influence than females.…”
Section: Influencementioning
confidence: 59%
“…Research indicates that males exert more influence over the decision making process. 29 The literature confirmed many common gender findings, such as men describing themselves as having a higher ability to influence others, and peers viewing males as having higher influencing ability. …”
mentioning
confidence: 63%
“…Harbaugh et al (2003), or Gneezy et al (forthcoming)) others have argued that the differences are due to biological distinctions (see e.g. Bateup et al (2002), Buser (2012), or Colarelli et al (2006)). Croson and Gneezy (2009) conclude on page 467 "that both nature and nuture are responsible for the gender differences in competition.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, by recourse to hypotheses from sociobiology and evolutionary psychology, recent research in organization science has already identified several effects of pre-adaptations on social behavior. Gender-specific pre-adaptations seem to be behind such phenomena as occupational segregation (Browne, 2006) and status segregation (Colarelli, Spranger and Hechanova, 2006). Organizational citizenship behavior may be due to pre-adapted behavior that signals individual superiority according to the handicap principle discussed in biology (Deutsch Salomon and Deutsch, 2006).…”
Section: Introductionmentioning
confidence: 99%